Thermal Durability Characterization of a Simple Polymethyl-methacrylate (PMMA) Based-Optical Waveguide - Yulianti, Ian; Purwinarko, Aji; Widiarti, Nuni; Ngajikin, Nor Hafizah; Insan , Shiva Maulana Khoiru; Putra, Ngurah Made Darma (Universitas Negeri Surabaya, 2024)
Polymethyl-methacrylate (PMMA)-based optical waveguide is a good candidate for a simple and low-cost waveguide. However, the thermal properties have not been investigated. In this work, thermal durability characterization of PMMA-based waveguide was carried out. Waveguide fabrication process was done in three stages, which are patterning the PMMA cladding, core material synthetization and core material application to the cladding. Core pattern with cross section area of 1×1 mm2 was engraved on the 4 cm long PMMA sheet. Unsaturated polyester resin (UPR) was used as a core material. Characterizations were conducted for temperature dependent loss (TDL), temperature working range, and long exposure durability. For TDL characterization, the temperature varied from 30°C to 75°C. Meanwhile, for temperature working range, the waveguide was exposed to cycled heating. The thermal durability characterization was done by immersing the waveguide in distilled water at temperature of 40 °C for 288 hours. The results showed that a little change of output intensity occurred due to temperature variation with TDL of 0.0235 dB/°C. The maximum limit of the temperature is 70°C. For long exposure to temperature of 40oC, the results showed that the waveguide has a good performance.